OPTIMASI KOMBINASI KARBOPOL 940 DAN HIDROKSIPROPIL METILSELULOSA (HPMC) TERHADAP EFEKTIVITAS GEL ANTISEPTIK FRAKSI ETIL ASETAT DAUN KESUM (Polygonum minus Huds.) DENGAN METODE SIMPLEX LATTICE DESIGN - ., Deasy Natasya (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Kesum (Polygonum minus Huds.) leaves have been investigated have antibacterial activity. Thisresearch was done to optimize the exploration of kesum plant by knowing that the ethyl acetate fraction ofKesum had antibacterial activity and how its effectiveness after it was formulated in gel with the optimumcombination of HPMC and Carbopol 940 by the Simplex Lattice Design (SLD) method. Extraction of kesumleave was done by maseration method, then was fractionated using n-hexane, ethyl acetate and methanolsolvent. The effectiveness test was done to ethyl acetate fraction by determination at the measurement of theinhibition by clear zone. One Way ANOVA test at concentration 5%, 10% and 15% indicated that the 10%concentration gives the optimum inhibition and will be formulated in a gel form. Based on the test of gel A(100% Carbopol- 0% HPMC); gel B (0% Carbopol - 100% HPMC); and gel C (50% Carbopol 50%HPMC) was obtained the best combination was Carbopol 940 100% - HPMC 0%. The data was analyzedstatistically using SPSS Version 17 with signification value p>0,05, the Simplex Lattice Design method canbe used to predict the optimum formulation. While comparison with positive control was obtained thesignificant value p>0,05 showed there was no a significant difference between optimum gel and positivecontrol. Based on the results of the analysis with paired samples t-test was obtained significance valuep<0,05. This means that there was no significant inhibition difference between the ethyl acetate fractionwithout formulation with the ethyl acetate fraction that have been formulated into gel form. Gel of theoptimum formula has a good physical and chemical properties.Key words : Kesum leaves, Ethyl acetate fraction, Gel, Simplex Lattice Design